2021
DOI: 10.1007/s00259-021-05379-z
|View full text |Cite
|
Sign up to set email alerts
|

TSPO imaging in animal models of brain diseases

Abstract: Over the last 30 years, the 18-kDa TSPO protein has been considered as the PET imaging biomarker of reference to measure increased neuroinflammation. Generally assumed to image activated microglia, TSPO has also been detected in endothelial cells and activated astrocytes. Here, we provide an exhaustive overview of the recent literature on the TSPO-PET imaging (i) in the search and development of new TSPO tracers and (ii) in the understanding of acute and chronic neuroinflammation in animal models of neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 199 publications
(312 reference statements)
0
40
0
Order By: Relevance
“…87 This is partly due to human TSPO polymorphisms causing differential affinity for TSPO ligands, although this does not appear to be an issue in preclinical animal studies. 87,88…”
Section: Imaging Markers Of Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…87 This is partly due to human TSPO polymorphisms causing differential affinity for TSPO ligands, although this does not appear to be an issue in preclinical animal studies. 87,88…”
Section: Imaging Markers Of Neuroinflammationmentioning
confidence: 99%
“…87 This is partly due to human TSPO polymorphisms causing differential affinity for TSPO ligands, although this does not appear to be an issue in preclinical animal studies. 87,88 PET studies in animal models and patients have shown that TSPO expression is low in the first days after stroke, increases in the following weeks (Figure 2, middle), and normalizes again after several months. 88,89 Nevertheless, activation of microglia, colocalized with secondary tissue degeneration, has been detected in noninfarcted areas of chronic patients beyond 6 to 12 months after stroke.…”
Section: Immune Cell Imagingmentioning
confidence: 99%
“…The most widely used neuroinflammation probes are those targeting at 18 kDa Translocator Protein (TSPO), locates on the outer mitochondrial membrane, and overexpressed by microglia during activation ( Van Camp et al, 2021 ; Zhou R. et al, 2021 ). TSPO PET tracers that have been applied in tau animal models include first generation (R)-[ 11 C]PK11195, second generation [ 18 F]FEBMP, [ 18 F]DPA-714, [ 11 C]AC-5216, ( 125 I) CLINDE, [ 11 C]PBR28, [ 18 F]FEDAA1106, and [ 11 C]DAA1106 ( Ji et al, 2008 , 2021 ; Maeda et al, 2011 ; Jacobs and Tavitian, 2012 ; Mirzaei et al, 2016 ; Ishikawa et al, 2018 ; Tournier et al, 2019 , 2020 ; Barron et al, 2020 ; Takuwa et al, 2020 ; Chaney et al, 2021 ; Fairley et al, 2021 ; Leng and Edison, 2021 ; Zhou X. et al, 2021 ), and third generation [ 18 F]GE-180, etc.…”
Section: Neuroinflammation Imagingmentioning
confidence: 99%
“…Several recent articles have provided thorough reviews on neuroinflammation PET imaging in AD patients and AD animal models [16,[176][177][178][179][180]. Thus here we discuss briefly the recent development in neuroinflammation imaging in AD amyloidosis animal models.…”
Section: Neuroinflammation Imagingmentioning
confidence: 99%